The Euro and the Battle of Ideas - Brunnermeier, Markus Konrad; Landau, Jean-Pierre; James, Harold, 1956- (Book collections on Project MUSE., 2016)
"Why is Europe's great monetary endeavor, the Euro, in trouble? A string of economic difficulties in Greece, Ireland, Spain, Italy, and other Eurozone nations has left observers wondering whether the currency union can survive. In this book, Markus Brunnermeier, Harold James, and Jean-Pierre Landau argue that the core problem with the Euro lies in the philosophical differences between the founding countries of the Eurozone, particularly Germany and France. But the authors also show how these seemingly incompatible differences can be reconciled to ensure Europe survival. As the authors demonstrate, Germany, a federal state with strong regional governments, saw the Maastricht Treaty, the framework for the Euro, as a set of rules. France, on the other hand, with a more centralized system of government, saw the framework as flexible, to be overseen by governments. The authors discuss how the troubles faced by the Euro have led its member states to focus on national, as opposed to collective, responses, a reaction explained by the resurgence of the battle of economic ideas: rules vs. discretion, liability vs. solidarity, solvency vs. liquidity, austerity vs. stimulus. Weaving together economic analysis and historical reflection, The Euro and the Battle of Ideas provides a forensic investigation and a road map for Europe's future."--Publisher's description